A Gas Kinetic Scheme for the Simulation of Compressible Multicomponent Flows (Communications in Computational Physics, 2013)
In this paper, a gas kinetic scheme for the compressible multicomponentflows is presented by making use of two-species BGK model in [A. D. Kotelnikov andD. C. Montgomery, A Kinetic Method for Computing Inhomogeneous Fluid Behavior,J. Comput. Phys. 134 (1997) 364-388]. Different from the conventional BGK model,the collisions between different species are taken into consideration. Based on theChapman-Enskog expansion, the corresponding macroscopic equations are derivedfrom this two-species model. Because of the relaxation terms in the governing equations, the method of operator splitting is applied. In the hyperbolic part, the integralsolutions of the BGK equations are used to construct the numerical fluxes at the cellinterface in the framework of finite volume method. Numerical tests are presentedin this paper to validate the current approach for the compressible multicomponentflows. The theoretical analysis on the spurious oscillations at the interface is also presented.